The Effectiveness of Interventions to Increase Parent Involvement in Special Education: A Systematic Literature Review and Meta-Analysis. Issue 2 (3rd April 2017) - Goldman, Samantha E.; Burke, Meghan M.
ABSTRACT: Although parent involvement is required by special education law and is important for all students, the literature synthesizing studies on parent involvement has focused on the general education parent population, often without addressing students with disabilities. The purpose of this review was to descriptively synthesize the literature on parent training interventions to increase parent involvement for parents of school-aged students with disabilities and to evaluate the effects of this intervention using meta-analysis. The literature on parent involvement interventions was minimal, with few recent peer-reviewed studies; all included studies focused on parent involvement in the context of Individualized Education Program (IEP) meetings. Results of the random effects model were not significant, with a weighted mean effect size of 0.26 (95% CI [–1.01, 1.53]). Results are discussed in the context of low heterogeneity across studies and implications for future research, including the need for novel interventions to increase parent participation in IEP meetings as well as studies focusing on parent involvement in other contexts for parents of children with disabilities.